Preparation method and product of ultrahigh-temperature suspension stabilizer and application of ultrahigh-temperature suspension stabilizer in oil well cement

By preparing an ultra-high temperature suspension stabilizer prepared by polymerization of 2-acrylamide-2-methylpropanesulfonic acid monomer, temperature-sensitive monomer and N-vinylpyrrolidone monomer, the problem that the prior art is difficult to maintain the stability of cement slurry under ultra-high temperature environment, and the dual effects of cement slurry stability under conditions above 200°C and the consistency control at room temperature are achieved.

CN119505082AActive Publication Date: 2025-02-25TIANJIN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411661855.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-25
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

Existing suspension stabilizers are difficult to effectively maintain the suspension stability of cement slurry under ultra-high temperature environments, especially at conditions above 200°C.

Method used

An ultra-high temperature suspension stabilizer is prepared by preparing a polymerization reaction from 2-acrylamide-2-methylpropanesulfonic acid monomer, a thermosensitive monomer and N-vinylpyrrolidone monomer, and a powdered product is obtained by freeze-drying. The amount of this stabilizer added to the cement is 0.2% to 1% to improve the ultra-high temperature stability of the cement slurry.

Benefits of technology

This ultra-high temperature suspension stabilizer can maintain the stability of the cement slurry under conditions above 200°C, with the initial consistency not exceeding 40Bc, and does not cause the cement slurry consistency to be too large at room temperature, significantly improving the suspension stability of the ultra-high temperature cement slurry system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505082A_ABST
    Figure CN119505082A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of oil exploration, in particular to a preparation method of an ultra-high-temperature suspension stabilizer, a product and application of the ultra-high-temperature suspension stabilizer in oil well cement. The preparation method comprises the following steps: dissolving a 2-acrylamide-2-methylpropanesulfonic acid monomer, a temperature-sensitive monomer and an N-vinyl pyrrolidone monomer in water to obtain a monomer solution; adding an initiator into the monomer solution, and heating to 30-60 DEG C to obtain a mixed solution; adding a reducing agent into the mixed solution for reaction to obtain a polymer solution; and freeze-drying the polymer solution to obtain the ultrahigh-temperature suspension stabilizer. When the suspension stabilizer obtained by the preparation method is added into an oil well cement paste system, the suspension stability of the cement paste in an ultrahigh-temperature environment can be maintained, and the initial consistency of the cement paste is not too large. The raw materials are convenient and easy to obtain, the preparation method is simple, the application requirements are met, the suspension stability of an ultrahigh-temperature cement slurry system can be effectively improved, and the safety of well cementation operation is guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of petroleum exploration, and in particular to a preparation method of an ultra-high temperature suspension stabilizer, a product and application of the same in oil well cement. Background Art

[0002] Cementing operation is an important link in the development of oil and gas fields, and its quality is directly related to the production efficiency and safety of oil and gas wells. In the cementing process, the stability of cement slurry is one of the key factors to ensure the quality of cementing. With the continuous deepening of oil and gas exploration and development, deep and ultra-deep oil and gas resources have become important exploration targets. However, the high temperature and high pressure environment puts extremely high requirements on the performance of cement slurry. Under ultra-high temperature, water is in a supercritical state, its viscosity drops sharply, and the resistance to the sinking of particles in the system is reduced; the high temperature dilution effect of polymer admixtures is serious, and its supporting force and viscosity are greatly reduced; the thermal motion of solid phase particles is intensified and the aggregation between particles accelerates the sinking speed of particles. These factors will cause the system instability of cement slurry. Severe particle sedimentation will lead to an increase in the solid content at the bottom of the slurry column, an increase in consistency, an increase in density, a shortened thickening time, and a deterioration in the comprehensive performance of cement slurry; and more free liquid is produced in the upper layer, and a water ring or water belt is formed on the top of the cement slurry to provide an oil, gas and water channeling channel, which seriously affects the quality of interlayer isolation.

[0003] In engineering, suspension stabilizers are often added to alleviate the suspension instability of cement slurry and the water separation of cement slurry. Natural mineral ultra-high temperature suspension stabilizers mainly include some specially treated mineral materials, such as silica fume, metakaolin, etc. These mineral materials can form a stable suspension system at high temperature and have good high temperature resistance. At the same time, they can also form good compatibility with other admixtures to improve the overall performance of cement slurry. However, under ultra-high temperature environment, the thermal movement of inorganic suspension material particles intensifies and the viscosity of water decreases, resulting in reduced viscosity and collapse of the supporting skeleton. In addition, its hydration and dispersion ability in high-salt formation environment is severely inhibited, thereby reducing its efficiency in ultra-high temperature environment. Organic polymer materials are another commonly used suspension stabilizer, which can be dispersed in water to form an intertwined network structure. Its strong hydrophilic groups form hydrogen bonds with water molecules to adsorb water molecules, reduce the degree of freedom of water molecules, thereby increasing the liquid phase viscosity, increasing the viscosity between cement particles, increasing the static shear force of cement slurry, and improving the suspension stability of slurry. Natural polymer materials are greatly affected by temperature. Higher temperatures will cause natural organic polymer materials to degrade to varying degrees and affect the suspension stability of the slurry. Synthetic polymer suspension stabilizers can be produced according to product technical requirements through molecular structure design, selection of suitable functional monomers and special processing technology. These polymers can form a stable suspension system at high temperatures and have good temperature and salt resistance.

[0004] Although various types of suspension stabilizers currently available can meet the needs of high-temperature cement slurry systems of 140 to 180°C, they are rarely used in ultra-high-temperature cement slurry systems above 200°C. Summary of the invention

[0005] Based on the above content, the present invention provides a preparation method and product of an ultra-high temperature suspension stabilizer and its application in oil well cement. The cement slurry with the suspension stabilizer added will not have too high a consistency at room temperature (20°C), but can maintain a certain consistency at ultra-high temperature (above 200°C).

[0006] To achieve the above object, the present invention provides the following solutions:

[0007] One of the technical solutions of the present invention is a method for preparing an ultra-high temperature suspension stabilizer, comprising the following steps:

[0008] Step 1, dissolving 2-acrylamide-2-methylpropanesulfonic acid monomer, temperature-sensitive monomer, and N-vinyl pyrrolidone monomer in water to obtain a monomer solution;

[0009] Step 2, adding an initiator to the monomer solution and heating to 30-60° C. to obtain a mixed solution;

[0010] Step 3, adding a reducing agent to the mixed solution to react and obtain a polymer solution;

[0011] Step 4: freeze-drying the polymer solution to obtain the ultra-high temperature suspension stabilizer.

[0012] The second technical solution of the present invention is an ultra-high temperature suspension stabilizer prepared according to the above-mentioned preparation method.

[0013] The third technical solution of the present invention is the application of the above-mentioned ultra-high temperature suspension stabilizer in cementing engineering.

[0014] A fourth technical solution of the present invention is a cement slurry, the raw materials of which include the above-mentioned ultra-high temperature suspension stabilizer.

[0015] The present invention discloses the following technical effects:

[0016] 1. The preparation method of the present invention has a simple process, and the raw materials are cheap and readily available, which is conducive to large-scale production.

[0017] 2. Most of the existing suspension stabilizers are suitable for high-temperature cement slurry systems of 140 to 180°C. The present invention makes up for the defect that the existing suspension stabilizers cannot be used in ultra-high temperature cement slurry systems.

[0018] 3. Although some existing technologies can meet the suspension stability requirements of cement slurry at high temperatures, they will also increase the viscosity of cement slurry at room temperature, resulting in difficulty in mixing the slurry; the present invention makes up for this technical defect, so that the initial consistency of the cement slurry added with the suspension stabilizer does not exceed 40Bc, while maintaining suspension stability at ultra-high temperatures. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0020] Figure 1 This is a comparison chart of infrared spectra of the ultra-high temperature suspension stabilizers prepared in Example 1 and Example 4 of the present invention.

[0021] Figure 2 These are the thermogravimetric curves of the ultra-high temperature suspension stabilizers prepared in Examples 1 and 4 of the present invention; wherein (a) is Example 1, and (b) is Example 4. DETAILED DESCRIPTION

[0022] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0023] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0024] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0025] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0026] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0027] The first aspect of the present invention provides a method for preparing an ultrahigh temperature suspension stabilizer, comprising the following steps:

[0028] Step 1, dissolving 2-acrylamide-2-methylpropanesulfonic acid monomer, temperature-sensitive monomer, and N-vinyl pyrrolidone monomer in water to obtain a monomer solution;

[0029] Step 2, adding an initiator to the monomer solution and heating to 30-60° C. to obtain a mixed solution;

[0030] Step 3, adding a reducing agent to the mixed solution to react and obtain a polymer solution;

[0031] Step 4: freeze-drying the polymer solution to obtain the ultra-high temperature suspension stabilizer.

[0032] In a preferred embodiment of the present invention, the pH of the monomer solution is 6-7.

[0033] In the present invention, the pH of the monomer solution is regulated by adding an alkaline solution such as a NaOH solution.

[0034] In a preferred embodiment of the present invention, the temperature-sensitive monomer is N,N-diethylacrylamide, N,N-dimethylacrylamide or N-isopropylacrylamide.

[0035] In a preferred embodiment of the present invention, the mass ratio of the 2-acrylamide-2-methylpropanesulfonic acid monomer, the temperature-sensitive monomer and the N-vinyl pyrrolidone monomer is (28-30): (8-10): (1-2).

[0036] If the amount of the temperature-sensitive monomer and N-vinyl pyrrolidone added is too high, the molecular weight of the polymer will decrease significantly or even cause polymerization failure, making the prepared product unable to be used as a suspension stabilizer; if the amount of 2-acrylamide-2-methylpropane sulfonic acid monomer is too high and the amount of the temperature-sensitive monomer and N-vinyl pyrrolidone added is too low, the thermal stability of the prepared product will deteriorate and cannot meet the use requirement of 200°C.

[0037] The amount of water used in the present invention is 5-10 times the total mass of the monomers.

[0038] In a preferred embodiment of the present invention, the initiator is ammonium persulfate, potassium persulfate or azobisisobutylamidine hydrochloride; the reducing agent is tetramethylethylenediamine or sodium bisulfite.

[0039] In the present invention, the addition of a reducing agent allows the reaction to proceed at a lower temperature.

[0040] In a preferred embodiment of the present invention, the added amount of the initiator is 0.6wt% of the total mass of the 2-acrylamide-2-methylpropanesulfonic acid monomer, the temperature-sensitive monomer and the N-vinyl pyrrolidone monomer; and the molar ratio of the initiator to the reducing agent is 1:0.8.

[0041] In a preferred embodiment of the present invention, in step 3, the reaction temperature is 30-60°C; and the reaction time is 2-6h.

[0042] The reaction was carried out under stirring conditions; the stirring rate was 220 rpm±20 rpm.

[0043] The freeze-drying step further includes grinding into powder. The present invention has no special requirements on the particle size of the grinding, and the grinding into powder is sufficient.

[0044] The second aspect of the present invention provides an ultra-high temperature suspension stabilizer prepared according to the above preparation method.

[0045] A third aspect of the present invention provides an application of the ultra-high temperature suspension stabilizer in cementing engineering.

[0046] In cementing engineering, the ultrahigh temperature suspension stabilizer is added in an amount of 0.2% to 1% of the mass of the cement. The ultrahigh temperature suspension stabilizer of the present invention can meet the construction requirements of corresponding working conditions in cementing engineering, ensure cementing safety, and improve cementing quality.

[0047] A fourth aspect of the present invention provides a cement slurry, the raw materials of which include the above-mentioned ultra-high temperature suspension stabilizer.

[0048] The ultra-high temperature suspension stabilizer accounts for 0.2% to 1% of the mass of cement in the cement slurry.

[0049] The suspension stabilizer obtained by the preparation method of the present invention is added to the oil well cement slurry system, which can maintain the suspension stability of the cement slurry in an ultra-high temperature environment without making the initial viscosity of the cement slurry too large. The raw materials of the present invention are convenient and easy to obtain, the preparation method is simple, and the application requirements are met. It can effectively improve the suspension stability of the ultra-high temperature cement slurry system and ensure the safety of cementing operations.

[0050] The technical solutions described in the present invention, unless otherwise specified, are all conventional solutions in the art, and the reagents or raw materials used, unless otherwise specified, are purchased from commercial channels or have been disclosed.

[0051] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0052] Example 1

[0053] A method for preparing an ultra-high temperature suspension stabilizer for oil well cement, comprising the following steps:

[0054] Step 1, dissolving 28 g of 2-acrylamide-2-methylpropanesulfonic acid, 10 g of N,N-dimethylacrylamide, and 2 g of N-vinyl pyrrolidone in 160 g of deionized water in order by mass, adjusting the pH to 6.5 with a NaOH solution, and stirring to obtain a monomer solution;

[0055] Step 2, adding ammonium persulfate to the solution under stirring at 220 rpm ± 20 rpm, and heating to raise the system temperature. The amount of ammonium persulfate added is 0.6 wt% of the total weight of the monomer, and the system temperature is 30°C;

[0056] Step 3, adding tetramethylethylenediamine to the solution obtained in step 2, maintaining 30°C, and stirring at 220 rpm ± 20 rpm for 4 hours to obtain a polymer solution. The amount of tetramethylethylenediamine added is 0.8 (molar fraction) of the amount of ammonium persulfate added;

[0057] Step 4, freeze-drying the solution obtained in step 3, and grinding to obtain a white powder, which is an ultra-high temperature suspension stabilizer for oil well cement.

[0058] Step 5, suspension stability performance test: Test the cement slurry thickening curve at 200°C, 100MPa, and 90min. After the thickening experiment reaches the target temperature and pressure for 30min, turn off the motor, maintain at the experimental temperature and pressure for 30min, turn on the motor again, and record the recoil value of the instantaneous consistency at the start-up. After a period of time when the consistency is stable, stop the thickening experiment, lower the temperature to 90°C, remove it, stir it and pour it into a 250mL measuring cylinder, place it in a 90°C oven, take it out after curing for 2h, and measure the upper and lower density difference of the cement slurry. The cement slurry formula is: 500g of G-grade oil well cement + 35% 200 mesh quartz sand + 1% dispersant DRS-1S + 5% retarder GH-9 + 5% fluid loss reducer DRF-3L + 0.6% ultra-high temperature suspension stabilizer + 49.4% water (the percentages in the cement slurry formula all represent the mass percentage of G-grade oil well cement; the same below).

[0059] The structure of the ultra-high temperature suspension stabilizer prepared in Example 1 is as follows: Figure 1As shown; (a) represents embodiment 1, (b) represents embodiment 4. Figure 1 It can be seen that the product is the target product, different temperature-sensitive monomers can participate in the copolymerization and there is no monomer residue in the reaction.

[0060] Example 2

[0061] A method for preparing an ultra-high temperature suspension stabilizer for oil well cement, comprising the following steps:

[0062] Step 1, dissolving 28 g of 2-acrylamide-2-methylpropanesulfonic acid, 10 g of N,N-diethylacrylamide, and 2 g of N-vinylpyrrolidone in 160 g of deionized water in order by mass, adjusting the pH to 6.8 with a NaOH solution, and stirring to obtain a monomer solution;

[0063] Step 2, adding ammonium persulfate to the solution under stirring, and heating to raise the system temperature. The amount of ammonium persulfate added is 0.6wt% of the total weight of the monomers, and the system temperature is 60°C;

[0064] Step 3, stirring the solution obtained in step 2 at 60° C. for 0.5 h, raising the temperature to 80° C. after the temperature stabilizes, and stirring at 220 rpm±20 rpm for 4 h to obtain a polymer solution.

[0065] Step 4, freeze-drying the solution obtained in step 3, and grinding to obtain a white powder, which is an ultra-high temperature suspension stabilizer for oil well cement.

[0066] Step 5, suspension stability performance test: Test the cement slurry thickening curve at 200°C, 100MPa, and 90min. After the thickening experiment reaches the target temperature and pressure for 30min, turn off the motor, cure at the experimental temperature and pressure for 30min, turn on the motor again, and record the recoil value of the instantaneous consistency. After a period of time when the consistency is stable, stop the thickening experiment, lower the temperature to 90°C, remove it, stir it and pour it into a 250mL measuring cylinder, place it in a 90°C oven, take it out after curing for 2h, and measure the upper and lower density difference of the cement slurry. The cement slurry formula is: 500g of G-grade oil well cement + 35% 200 mesh quartz sand + 1% dispersant DRS-1S + 5% retarder GH-9 + 5% fluid loss reducer DRF-3L + 0.6% ultra-high temperature suspension stabilizer + 49.4% water.

[0067] Example 3

[0068] A method for preparing an ultra-high temperature suspension stabilizer for oil well cement, comprising the following steps:

[0069] Step 1, dissolving 30 g of 2-acrylamide-2-methylpropanesulfonic acid, 9 g of N,N-dimethylacrylamide, and 1 g of N-vinyl pyrrolidone monomers in 160 g of deionized water in order by mass, adjusting the pH to 6.6 with a NaOH solution, and stirring to obtain a monomer solution;

[0070] Step 2, adding ammonium persulfate to the solution under stirring, and heating to raise the system temperature. The amount of ammonium persulfate added is 0.6wt% of the total weight of the monomers, and the system temperature is 30°C;

[0071] Step 3, adding tetramethylethylenediamine to the solution obtained in step 2, maintaining 30° C., and stirring at 220 rpm±20 rpm for 6 hours to obtain a polymer solution, wherein the amount of tetramethylethylenediamine added is 0.8 (molar fraction) of the amount of ammonium persulfate added.

[0072] Step 4 is the same as step 4 in Example 1.

[0073] Example 4

[0074] A method for preparing an ultra-high temperature suspension stabilizer for oil well cement, comprising the following steps:

[0075] Step 1, dissolving 30 g of 2-acrylamide-2-methylpropanesulfonic acid, 8 g of N-isopropylacrylamide, and 2 g of N-vinylpyrrolidone monomers in 160 g of deionized water in order by mass, adjusting the pH to 6.6 with a NaOH solution, and stirring to obtain a monomer solution;

[0076] Step 2, adding ammonium persulfate to the solution under stirring, and heating to raise the system temperature. The amount of ammonium persulfate added is 0.6wt% of the total weight of the monomers, and the system temperature is 30°C;

[0077] Step 3, adding tetramethylethylenediamine to the solution obtained in step 2, maintaining 30°C, and stirring at 220 rpm ± 20 rpm for 4 hours to obtain a polymer solution. The amount of tetramethylethylenediamine added is 0.8 (molar fraction) of the amount of ammonium persulfate added;

[0078] Step 4, freeze-drying the solution obtained in step 3, and grinding to obtain a white powder, which is an ultra-high temperature suspension stabilizer for oil well cement.

[0079] Step 5, suspension stability performance test: Test the cement slurry thickening curve at 200°C, 100MPa, and 90min. After the thickening experiment reaches the target temperature and pressure for 30min, turn off the motor, cure at the experimental temperature and pressure for 30min, turn on the motor again, and record the recoil value of the instantaneous consistency. After a period of time when the consistency is stable, stop the thickening experiment, lower the temperature to 90°C, remove it, stir it and pour it into a 250mL measuring cylinder, place it in a 90°C oven, take it out after curing for 2h, and measure the upper and lower density difference of the cement slurry. The cement slurry formula is: 500g of G-grade oil well cement + 35% 200 mesh quartz sand + 1% dispersant DRS-1S + 5% retarder GH-9 + 5% fluid loss reducer DRF-3L + 0.6% ultra-high temperature suspension stabilizer + 49.4% water.

[0080] Comparative Example 1

[0081] Refer to Example 1, except that no ultrahigh temperature suspension stabilizer is added during the suspension stability performance test (ie, the preparation of the ultrahigh temperature suspension stabilizer is omitted, and the addition of the ultrahigh temperature suspension stabilizer is omitted during the suspension stability performance test).

[0082] Suspension stability performance test: Test the cement slurry thickening curve at 200℃, 100MPa, and 90min. After the thickening experiment reaches the target temperature and pressure for 30min, turn off the motor, cure at the experimental temperature and pressure for 30min, turn on the motor again, and record the recoil value of the instantaneous consistency. After a period of time when the consistency is stable, stop the thickening experiment, lower the temperature to 90℃, remove it, stir it, pour it into a 250mL measuring cylinder, place it in a 90℃ oven, take it out after curing for 2h, and measure the upper and lower density difference of the cement slurry. The cement slurry formula is: 500g of G-grade oil well cement + 35% 200 mesh quartz sand + 1% dispersant DRS-1S + 5% retarder GH-9 + 5% fluid loss reducer DRF-3L + 50% water.

[0083] Comparative Example 2

[0084] Refer to Example 1, except that different amounts of ultra-high temperature suspension stabilizer are added during the suspension stability performance test.

[0085] A method for preparing an ultra-high temperature suspension stabilizer for oil well cement, comprising the following steps:

[0086] Step 1, dissolving 28 g of 2-acrylamide-2-methylpropanesulfonic acid, 10 g of N,N-dimethylacrylamide, and 2 g of N-vinyl pyrrolidone in 160 g of deionized water in order by mass, adjusting the pH to 6.5 with a NaOH solution, and stirring to obtain a monomer solution;

[0087] Step 2, adding ammonium persulfate to the solution under stirring, and heating to raise the system temperature. The amount of ammonium persulfate added is 0.6wt% of the total weight of the monomers, and the temperature is 30°C;

[0088] Step 3, adding tetramethylethylenediamine to the solution obtained in step 2, maintaining 30°C, and stirring at 220 rpm ± 20 rpm for 4 hours to obtain a polymer solution. The amount of tetramethylethylenediamine added is 0.8 (molar fraction) of the amount of ammonium persulfate added;

[0089] Step 4, freeze-drying the solution obtained in step 3, and grinding to obtain a white powder, which is an ultra-high temperature suspension stabilizer for oil well cement.

[0090] Step 5, suspension stability performance test: Test the cement slurry thickening curve at 200°C, 100MPa, and 90min. After the thickening experiment reaches the target temperature and pressure for 30min, turn off the motor, cure at the experimental temperature and pressure for 30min, turn on the motor again, and record the recoil value of the instantaneous consistency at startup. After a period of time when the consistency is stable, stop the thickening experiment, lower the temperature to 90°C, remove it, stir it and pour it into a 250mL measuring cylinder, place it in a 90°C oven, take it out after curing for 2h, and measure the upper and lower density difference of the cement slurry. The cement slurry formula is: 500g of G-grade oil well cement + 35% 200 mesh quartz sand + 1% dispersant DRS-1S + 5% retarder GH-9 + 5% fluid loss reducer DRF-3L + 0.2% ultra-high temperature suspension stabilizer + 49.8% water.

[0091] Comparative Example 3

[0092] Refer to Example 1, except that different amounts of ultra-high temperature suspension stabilizer are added during the suspension stability performance test.

[0093] A method for preparing an ultra-high temperature suspension stabilizer for oil well cement, comprising the following steps:

[0094] Step 1, dissolving 28 g of 2-acrylamide-2-methylpropanesulfonic acid, 10 g of N,N-dimethylacrylamide, and 2 g of N-vinyl pyrrolidone in 160 g of deionized water in order by mass, adjusting the pH to 6.5 with a NaOH solution, and stirring to obtain a monomer solution;

[0095] Step 2, adding ammonium persulfate to the solution under stirring, and heating to raise the system temperature. The amount of ammonium persulfate added is 0.6wt% of the total weight of the monomers, and the temperature is 30°C;

[0096] Step 3, adding tetramethylethylenediamine to the solution obtained in step 2, maintaining 30°C, and stirring at 220 rpm ± 20 rpm for 4 hours to obtain a polymer solution. The amount of tetramethylethylenediamine added is 0.8 (molar fraction) of the amount of ammonium persulfate added;

[0097] Step 4, freeze-drying the solution obtained in step 3, and grinding to obtain a white powder, which is an ultra-high temperature suspension stabilizer for oil well cement.

[0098] Step 5, suspension stability performance test: Test the cement slurry thickening curve at 200°C, 100MPa, and 90min. After the thickening experiment reaches the target temperature and pressure for 30min, turn off the motor, cure at the experimental temperature and pressure for 30min, turn on the motor again, and record the recoil value of the instantaneous consistency at startup. After a period of time when the consistency is stable, stop the thickening experiment, lower the temperature to 90°C, remove it, stir it and pour it into a 250mL measuring cylinder, place it in a 90°C oven, take it out after curing for 2h, and measure the upper and lower density difference of the cement slurry. The cement slurry formula is: 500g of G-grade oil well cement + 35% 200 mesh quartz sand + 1% dispersant DRS-1S + 5% retarder GH-9 + 5% fluid loss reducer DRF-3L + 1% ultra-high temperature suspension stabilizer + 49% water.

[0099] Application performance testing

[0100] The infrared spectrum of the polymer prepared in Example 1 was tested using an FTIR infrared spectrometer. The results are as follows: Figure 2 As shown, the infrared test results show that all monomers participate in the polymerization and the product is the target product.

[0101] The polymers (ultra-high temperature suspension stabilizers) prepared in Examples 1 and 4 were subjected to thermal gravimetric tests using a thermal analyzer. The results are as follows: Figure 2 As shown, the thermogravimetric curves indicate that both ultra-high temperature suspension stabilizers have good high temperature resistance, and the temperature resistance reaches above 270°C.

[0102] The performance test results of Examples 1, 2, 4 and Comparative Examples 1, 2, 3 are shown in Table 1. The test content is the instantaneous recoil value of the cement thickening experiment and the density difference test of the upper and lower layers of cement slurry. The specific contents are as follows: Test the cement slurry thickening curve at 200°C, 100MPa, and 90min. Turn off the motor after the thickening experiment reaches the target temperature and pressure for 30min, cure at the experimental temperature and pressure for 30min, turn on the motor again, and record the recoil value of the instantaneous consistency at startup. After a period of time when the consistency is stable, stop the thickening experiment, reduce the temperature to 90°C, remove it, stir it and pour it into a 250mL measuring cylinder, place it in a 90°C oven, take it out after curing for 2h, and measure the density difference between the upper and lower layers of the cement slurry. Among them, the initial consistency of the cement slurry cannot exceed 40Bc, the qualified standard for the shutdown test is that the recoil value is less than 40Bc, and the qualified standard for the density difference test is that the density difference between the upper and lower layers is less than 0.05g / cm 3 .

[0103] Table 1 Sedimentation stability test results of ultra-high temperature suspension stabilizer

[0104]

[0105]

[0106] It can be concluded from Table 1 that the shutdown and density difference tests of the ultra-high temperature suspension stabilizers prepared by Examples 1, 2, and 4 of the present invention are all qualified and can meet the requirements; the shutdown and density difference tests of Comparative Example 1 without adding the ultra-high temperature suspension stabilizer are all unqualified; and when the ultra-high temperature suspension stabilizer is added in an amount less than 0.6%, although the density difference test can meet the requirements, the shutdown test is unqualified; except for Comparative Example 1, no free liquid is generated in the upper layer of cement in all density difference tests. The performance test results show that the ultra-high temperature suspension stabilizer prepared by the present invention can meet the sedimentation stability requirements of oil well cement at 200°C, making up for the problem of insufficient temperature resistance of existing suspension stabilizers, and at the same time has good compatibility with various other admixtures such as fluid loss reducers, retarders, etc., which is conducive to construction safety and does not affect the performance of cement.

[0107] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing an ultra-high temperature suspension stabilizer, characterized in that: The following steps are involved: Step 1, dissolving 2-acrylamide-2-methylpropanesulfonic acid monomer, temperature-sensitive monomer, and N-vinyl pyrrolidone monomer in water to obtain a monomer solution; Step 2, adding an initiator to the monomer solution and heating to 30-60° C. to obtain a mixed solution; Step 3, adding a reducing agent to the mixed solution to react and obtain a polymer solution; Step 4: freeze-drying the polymer solution to obtain the ultra-high temperature suspension stabilizer.

2. The method for preparing the ultrahigh temperature suspension stabilizer according to claim 1, characterized in that: The pH of the monomer solution is 6-7.

3. The method for preparing the ultrahigh temperature suspension stabilizer according to claim 1, characterized in that: The temperature-sensitive monomer is N,N-diethylacrylamide, N,N-dimethylacrylamide or N-isopropylacrylamide.

4. The method for preparing the ultrahigh temperature suspension stabilizer according to claim 1, characterized in that: The mass ratio of the 2-acrylamide-2-methylpropanesulfonic acid monomer, the temperature-sensitive monomer and the N-vinyl pyrrolidone monomer is (28-30): (8-10): (1-2).

5. The method for preparing the ultrahigh temperature suspension stabilizer according to claim 1, characterized in that: The initiator is ammonium persulfate, potassium persulfate or azobisisobutylamidine hydrochloride; the reducing agent is tetramethylethylenediamine or sodium bisulfite.

6. The method for preparing the ultrahigh temperature suspension stabilizer according to claim 1, characterized in that: The added amount of the initiator is 0.6wt% of the total mass of the 2-acrylamide-2-methylpropanesulfonic acid monomer, the temperature-sensitive monomer and the N-vinyl pyrrolidone monomer; the molar ratio of the initiator to the reducing agent is 1:0.

8.

7. The method for preparing the ultrahigh temperature suspension stabilizer according to claim 1, characterized in that: In step 3, the reaction temperature is 30-60° C., and the reaction time is 2-6 h.

8. The ultra-high temperature suspension stabilizer prepared according to the preparation method according to any one of claims 1 to 7.

9. Use of the ultra-high temperature suspension stabilizer as claimed in claim 8 in cementing engineering.

10. A cement slurry, characterized in that: The raw materials include the ultra-high temperature suspension stabilizer described in claim 8.

Citation Information

Patent Citations

  • Temperature-sensitive fluid loss agent for well cementation cement slurry and preparation method of temperature-sensitive fluid loss agent

    CN115417950A

  • Preparation method and application of ultrahigh-temperature-resistant oil well cement suspension stabilizer for well cementation

    CN118772351A